2018
DOI: 10.1111/ijau.12121
|View full text |Cite
|
Sign up to set email alerts
|

Investors' perceptions of nonaudit services and their type in Germany: The financial crisis as a turning point

Abstract: As a result of mistrust in the auditing profession, legislators and regulators continue to impose restrictions to the joint provision of audit and nonaudit services (NAS) to protect investors' interests. However, investors may perceive NAS differently than legislators, and it is an open question whether a ban on NAS always aligns with investors' interests. Little evidence exists on investors' perceptions of auditor‐provided NAS in the continental European regulatory environment, including Germany. The unique f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…Several studies also establish a negative association (e.g., Krishnan, ; Gul et al ., ), whereas other studies only find a significant relation under restrictive conditions (e.g., Higgs and Skantz, ; Eilifsen and Knivsflå, ) or do not find an association (e.g., Ghosh et al ., ). For Germany, prior research indicates a negative impact of high non‐audit fees on audit quality (Quick and Sattler, ; Krauss and Zülch, , Eilifsen et al ., ). This could be due particularly to the German institutional setting with its lower investor protection and lower auditor litigation risk.…”
Section: Prior Literature and Hypothesesmentioning
confidence: 97%
“…Several studies also establish a negative association (e.g., Krishnan, ; Gul et al ., ), whereas other studies only find a significant relation under restrictive conditions (e.g., Higgs and Skantz, ; Eilifsen and Knivsflå, ) or do not find an association (e.g., Ghosh et al ., ). For Germany, prior research indicates a negative impact of high non‐audit fees on audit quality (Quick and Sattler, ; Krauss and Zülch, , Eilifsen et al ., ). This could be due particularly to the German institutional setting with its lower investor protection and lower auditor litigation risk.…”
Section: Prior Literature and Hypothesesmentioning
confidence: 97%
“…First, there is a need to revisit prior research topics, because we cannot assume that results remain stable after such an enormous regulatory reform. This was demonstrated by Eilifsen, Quick, Schmidt, and Umlauf (), who showed that capital market reactions to nonaudit service fees were reversed after the financial crisis, which may also be caused by an anticipation of stricter rules. Moreover, it is quite possible that the environmental setting under which research is conducted impacts the results.…”
mentioning
confidence: 89%
“…In However, the new regulation seems unnecessary, considering the empirical findings in the EU, which show little impairment of independence due to APTS, using data from the pre-2016 regime (Castillo-Merino et al, 2020;Eilifsen et al, 2018;Garcia-Blandon et al, 2017Watrin et al, 2019).…”
Section: Eumentioning
confidence: 99%